O enfrentamento da violência contra as meninas e mulheres na escola: análise do programa “Violência contra a mulher não é normal” - Santos, Mariana Lopes dos (Universidade Federal de São Carlos, 2025)
The program “Violence Against Women is Not Normal”, implemented by the São Paulo State Department of Education (SEDUC-SP) between January and July 2022, was analyzed in this dissertation from a critical perspective grounded in feminist studies, highlighting its potential and limitations. The initiative included the distribution of physical and digital booklets, as well as a training track made available on the São Paulo Education Media Center (CMSP) platform and was carried out in partnership with the Serenas Institute within the framework of the School Coexistence and Protection Improvement Program (CONVIVA SP), aimed at transforming schools into welcoming and safe spaces. Supervisors of education played a central role in monitoring and promoting educational actions and contributed to the collection of data on gender-based violence in schools through tools such as the CONVIVA SP Application (PLACON) and the Escola Total BI dashboard. The research, qualitative and interdisciplinary in nature, utilized documentary analysis of the program’s official materials and a bibliographic review of databases such as CAPES and ANPEd, as well as reports from the Brazilian Public Security Forum and the Patrícia Galvão Institute, to reflect on gender relations and education in the context of increasing rates of violence against girls and women in Brazil in 2022 and 2023. The results revealed significant gaps in the collection and availability of specific data on the educational platforms, which hindered the effectiveness of the proposed preventive and educational actions, particularly due to the absence of detailed information on gender-based violence, thus limiting the work of supervisors and school managers in formulating effective strategies. Furthermore, both the in-person and online training sessions showed insufficient reach, and while the booklets were relevant, they addressed the topic superficially, failing to foster critical reflections or propose transformative actions. It is concluded that, to promote structural changes, it is essential to expand the reach of training initiatives, integrate engaged pedagogical practices that encourage critical analysis, and improve monitoring and data analysis mechanisms to support more effective and inclusive public policies. This study reinforces the need to strengthen the role of schools as spaces for social transformation and protection, contributing to the construction of a fairer and more egalitarian society where women's rights are effectively promoted and defended.
Confronting violence against girls and women at school: analysis of the program “Violence against women is not normal”
Keywords: Violência contra mulheres e meninas; Pedagogia engajada; Supervisão de ensino; Relações de gênero na escola; Feminismos; Violence against women and girls; Engaged pedagogy; Teaching supervision; Gender relations in schools; Feminisms; CIENCIAS HUMANAS::EDUCACAO::ADMINISTRACAO EDUCACIONAL